PALEOENVIRONMENTAL ANALYSIS AND CYCLICITY OF THE MUSTAHIL FORMATION (CRETACEOUS OF CENTRAL SOMALIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
The Cretaceous Mustahil Formation is a marlstone-limestone unit, outcropping typically in the Fafan Valley of Ogaden (eastern Africa). A Mustahil section, measured at Bur Bitthale near Belet Uen (Central Somalia), is here described. The succession, dated as Late Aptian to Early-Middle Albian age on the basis of good faunal evidence (Orbitolina texana and Orbitolina sulxoncava), consists of two well developed thickeningcoarsening sequences, where four different facies have been recognized. The cap of both sequences is represented by a rudistid framework dominated by Eoradiolites lyratus. We interpret these cycles as shoaling up parasequences, which are the result of two depositional regressions produced by the progradation of broad shallowwater carbonate systems over the adjacent ramp and deep shelf.
Keywords: Paleoenvironmental analysis; cyclicity; rudistid reef; Early Cretaceous; Somalia